3D genome organization: a role for phase separation and loop extrusion?. (April 2019) - Stam, Maike; Tark-Dame, Mariliis; Fransz, Paul
Highlights: The 3D genome organization in plants and animals is very similar. Distant regulatory elements and target genes interact through physical interactions. Chromatin domains are formed based on transcription level and epigenetic landscape. Phase separation, and maybe loop extrusion, underly the plant genome organization. In plants loops can occur between active TADs that are separated by inactive TADs. Abstract : In eukaryotes, genomic information is encoded in chromosomes, which occupy distinct territories within the nucleus. Inside these territories, chromosomes are folded in a hierarchical set of topological structures, called compartments, topologically associated domains and loops. Phase separation and loop extrusion are the mechanisms indicated to mediate the 3D organization of the genome, and gene activity and epigenetic marks determine the activity level of the formed chromatin domains. The main difference between plants and animals may be the absence of canonical insulator elements in plants. Comparison across plant species indicates that the identification of chromatin domains is affected by genome size, gene density, and the linear distribution of genes and transposable elements.